2009
DOI: 10.1590/s0036-46652009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum beta-lactamases among Enterobacteriaceae isolated in a public hospital in Brazil

Abstract: SUMMARYExtended-spectrum β-lactamases (ESBL) in enterobacteria are recognized worldwide as a great hospital problem. In this study, 127 ESBL-producing Enterobacteriaceae isolated in one year from inpatients and outpatients at a public teaching hospital at São Paulo, Brazil, were submitted to analysis by PCR with specific primers for bla SHV , bla TEM and bla CTX-M genes. From the 127 isolates, 96 (75.6%) Klebsiella pneumoniae, 12 (9.3%) Escherichia coli, 8 (6.2%) Morganella morganii, 3 (2.3%) Proteus mirabilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
4
16
0
2
Order By: Relevance
“…During our one year study, most of the K. pneumoniae was isolated from patients with urinary tract infection at inpatient department. The prevalence of Klebsiella among hospitalized patients has been reported by other investigators from different countries including France, Turkey, Brazil and India [2,3,5,19]. Similar to our study (58.9 % ESBL), reports from other parts of India and other Asian countries have demonstrated comparable prevalence of ESBL K. pneumoniae (40-83.3 and 60 % respectively) whereas much lower prevalence is noted in western countries [5][6][7]20].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…During our one year study, most of the K. pneumoniae was isolated from patients with urinary tract infection at inpatient department. The prevalence of Klebsiella among hospitalized patients has been reported by other investigators from different countries including France, Turkey, Brazil and India [2,3,5,19]. Similar to our study (58.9 % ESBL), reports from other parts of India and other Asian countries have demonstrated comparable prevalence of ESBL K. pneumoniae (40-83.3 and 60 % respectively) whereas much lower prevalence is noted in western countries [5][6][7]20].…”
Section: Discussionmentioning
confidence: 78%
“…Resistance against beta-lactam and quinolone group of drugs, widely used for their treatment is mainly acquired by intra or inter species exchange of transferable plasmid encoded antibiotic resistant genes (viz bla TEM , bla SHV , bla CTX-M , QNR A, QNR B, and QNR S) [2]. Currently C150 TEM, C88 SHV, C69 CTX-M types variants has been described [3]. Six QNR A (QNR A1-QNR A6), 20 QNR B (QNR B1-QNR B20) and 3 QNR S variants (QNR S1-QNR S3) have been identified worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-eight non-clonal ESBL-producing Enterobacteriaceae strains, previously isolated [17] in a hospital set and representing, according to the institution's infection control committee, hospital infections (n = 9), community-acquired infections (n = 4), and colonization strains (n=15), were selected based on their distinct PFGE profiles and the detection of bla CTX-M genes by polymerase chain reaction (PCR) [18]. These non-clonal strains were selected in order to demonstrate the mobility and spread potential of CTX-M-encoding genes even when there is no clonal dissemination.…”
Section: Methodsmentioning
confidence: 99%
“…expasy.org/tools/ translate) showed that the isolate harbored bla KPC-2 and bla TEM-1 (GenBank accession numbers KC736925 and KF811201). bla TEM has been described in P. mirabilis from Brazil by Dropa et al (10) and Abreu et al (11) , but they did not sequence the gene. The analysis of antimicrobial agents revealed susceptibility to meropenem, polymyxin, and tigecycline.…”
mentioning
confidence: 98%